2017
DOI: 10.15560/13.4.267
|View full text |Cite
|
Sign up to set email alerts
|

The genus Anisancylus Pilsbry, 1924 (Planorboidea, Ancylinae) in South America: species distribution and new records

Abstract: Information on the distribution of Anisancylus Pilsbry, 1924 in South America is provided. For first time, we recorded A. dutrae (Santos 1994) in Minas Gerais state and 2 new localities in northeastern Brazil. Anisancylus obliquus (Broderip & Sowerby, 1832) is widely distributed in Chile, Peru, central and southern Argentina, Uruguay and southern Brazil while A. dutrae is restricted to Brazil. This freshwater genus shows a disjunct distribution in South America that could be explained by tectonics and evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, since there are significant differences between the densities of L. fortunei between the five sampled sites, we observed that our results agree with those proposed by Sylvester et al (2007) and where the higher the density of L. fortunei, the higher the density of H. piscium (BAL) and the lower the density of L. fortunei, the higher the richness of species is recorded (IMG). Silva et al (2020), in experiments on the Uruguay River, and an environment like IMG, highlight that the presence of predatory fish reduces the (Ovando et al 2017). On this site, IMG, 27 species of mollusks were already recorded, the product of years of campaigns by various researchers (Martín and Negrete 2006;Cesar et al 2012).…”
Section: Discussionmentioning
confidence: 75%
“…However, since there are significant differences between the densities of L. fortunei between the five sampled sites, we observed that our results agree with those proposed by Sylvester et al (2007) and where the higher the density of L. fortunei, the higher the density of H. piscium (BAL) and the lower the density of L. fortunei, the higher the richness of species is recorded (IMG). Silva et al (2020), in experiments on the Uruguay River, and an environment like IMG, highlight that the presence of predatory fish reduces the (Ovando et al 2017). On this site, IMG, 27 species of mollusks were already recorded, the product of years of campaigns by various researchers (Martín and Negrete 2006;Cesar et al 2012).…”
Section: Discussionmentioning
confidence: 75%